Pityriasis lichenoides chronica: case reports – the role of infectious agents? - Chiriac, Anca; Suditu, Gabriela; Mihaila, Doina; Chirana, Alice; Chiriac, Anca E.; Foia, Liliana; Solovan, Caius; Brzeziński, Piotr (Dermatology Review/Przegląd Dermatologiczny, 2014)
Introduction. pityriasis lichenoides chronica (PLC), which is a benign eruption with lymphocytic infiltrates of the skin, presents as a persistent, erythematous, papular eruption with scale. Patients may have guttate, hypopigmented macules with scale in addition to papules. It is related histopathologically to pityriasis lichenoides et varioliformis acuta (PLEVA), which presents as a recurrent papulonecrotic eruption. The PLC is a cutaneous disease of unknown etiology that most commonly affects children and young adults. The highly variable presentation of this condition often poses a diagnostic challenge. Objective. Presentation of two adults with PLC probably induced by infectious agents. Case reports. A woman presented with scaly, pruritic, erythematous-to-brown flattened papules, which varied in size from 3 mm to 1 cm, on the trunk and extremities, being first diagnosed as guttate psoriasis. A man sought medical advice for a disseminated eruption on the trunk and extremities, observed for 2 months before the consultation. He was in a good medical state, with no comorbidities and no medication. He complained of discrete pruritus and urethral discharge for many days. Conclusions. Pityriasis lichenoides may have arisen secondarily to these infections or there were two simultaneous diseases. Further studies must elucidate the role of infectious agents in this pathology.